Health care seeking behaviour among caregivers of children with pneumonia in a rural area - Kamaruzaman, Nor Azam; Muthupalaniappen, Leelavathi; Pasi, Hafizah (Japan International Cultural Exchange Foundation (JICEF), 2013)
Objective: The aim of this study is to evaluate caregiver's health seeking behaviour for children with pneumonia and to determine the associated factors. Design: This cross-sectional study was conducted at Hospital Semporna, East Malaysia from September 2009 to January 2010. Materials and Methods: Children diagnosed with pneumonia between ages 2 months to 5 years and their caregivers were selected. Pneumonia is classified using the modified IMCI and WHO classification used locally while health seeking behaviour was assessed using Health Care Utilization Model by Weller et al. Results: A total of 160 children with pneumonia and their caregivers participated in this study. Mean age of children with pneumonia is 21.8 ± 16.3 months. Males and females were equally affected (1.3:1). Majority had mild pneumonia (78.1%; n = 125). Mean duration of illness presentation is 3.47 ± 2.63 days. Caregivers are mostly females (88.8%, n = 142), received primary or secondary level of education (78.1%, n = 125) and belong to poor socioeconomic background (80.0%, n = 128). Most caregivers (87.5%, n = 140) practice self care or consult Health Care Provide (HCP) at government health clinics before seeking hospital treatment. Antipyrexial is the most common self medication used. This study found that severe pneumonia was more common among children with Very Low Weight for Age (VLWA) (p = 0.008) and those who received antibiotic preceding hospital visit (OR 3.93; 1.44; 9.67, p = 0.012). Conclusion: In general, caregivers attending to children with pneumonia in this study demonstrate reasonably good health seeking behaviour although they are from poor socioeconomic and variable cultural backgrounds in a rural area.